Unique Presentation of Giant Metastatic Microcystic Serous Adenocarcinoma of the Pancreas - Cyriac Abby Philips; Chetan Ramesh Kalal; Chhagan Bihari; Amrish Sahney; KN Chandan Kumar; Archana Rastogi (Case Reports in Gastrointestinal Medicine)
Tumors of the pancreas that contain substantial cystic components include mainly mucinous cystic neoplasm, intraductal papillary mucinous neoplasm, solid pseudopapillary tumor, and cystadenomas (which encompass microcystic, macrocystic/oligocystic, and rare solid serous adenomas). Microcystic adenoma of the pancreas is a tumor that is benign in nature. Malignant transformation in the tumor with metastases is rare and only about 26 cases have been reported so far. Here we present a giant microcystic adenoma of the pancreas, possibly the largest ever malignant type in this group ever reported in the literature with extensive metastases to the liver and causing extensive compression and encasement on surrounding structures.